A rose by another name? Characteristics that distinguish headache secondary to temporomandibular disorder from headache that is comorbid with temporomandibular disorder. Issue 4 (30th April 2023) - Sharma, Sonia; Slade, Gary D.; Fillingim, Roger B.; Ohrbach, Richard
Abstract : Supplemental Digital Content is Available in the Text. Coexistence of painful temporomandibular disorder and headache attributed to temporomandibular disorder increases the biopsychosocial burden of primary headache, highlighting the importance of comprehensive assessment and differential management. Abstract: Co-occurring pain conditions that affect overlapping body regions are complicated by the distinction between primary vs secondary pain conditions. We investigate the occurrence of headache and painful temporomandibular disorder (TMD) in a community-based, cross-sectional study of US adults in the Orofacial Pain: Prospective Evaluation and Risk Assessment (OPPERA-II) study. A specific goal was to determine whether headache attributed to TMD is separable from primary headache. Using DC/TMD and International Classification of Headache Disorders—third edition criteria, 3 groups of individuals were created: (a) headache without TMD; (b) headache comorbid with TMD; and (c) headache attributed to TMD. Regression models compared study groups according to demographic and comorbid characteristics, and post hoc contrasts tested for differences. Descriptive statistics and Cohen d effect size were computed, by group, for each predictor variable. Differences in continuous predictors were analyzed using one-way analysis of variance. Nearly all demographic and comorbid variables distinguished the combined headache and TMD groups from the group with headache alone. Relative to the reference group with primary headache alone, markers related to headache, TMD, somatic pain processing, psychosocial, and health conditions were substantially greater in both headache comorbid with TMD and headache attributed to TMD, attesting to their qualitative similarities. However, effect sizes relative to the reference group were large for headache comorbid with TMD and larger again for headache attributed to TMD, attesting to their separability in quantitative terms. In summary, the presence of overlapping painful TMD and headache adds substantially to the biopsychosocial burden of headache and points to the importance of comprehensive assessment and differential management.